Evaluation of different laboratory methods for isolation of bacteria and fungi in patients with continuous ambulatory peritoneal dialysis-associated peritonitis - Ahmadi, Shahram (2013)
Continuous ambulatory peritoneal dialysis (CAPD) is a common and safe method to dialyze waste metabolites in the patients with end stage renal failure (ESRF). Peritonitis is the most important complication of CAPD, leading to increased morbidity and mortality with an annual death rate of 15.6% in Malaysia in 2011. A non-conclusive laboratory identification of etiological agents with increased prevalence of culture-negative samples, leading to non-specific antimicrobial therapy and contributes to the increased mortality of peritonitis. In order to reduce the incidence rate of culture-negative peritonitis, this study was aimed to improve the laboratory diagnosis of peritonitis through modifying the existing sample collection, processing and culturing methods, utilizing a molecular method using the 16S rRNA typing approach for the direct detection (without culture) of the etiological agents from the peritoneal fluid and to determine the antibiotic susceptibility patterns of the bacteria isolated from patients with CAPD associated peritonitis. Among 91 peritoneal fluid specimens obtained from CAPD patients with clinical symptoms peritonitis admitted to Hospital Serdang from June 2011 to May 2012, 45 were confirmed as peritonitis based on International Society Peritoneal Dialysis (ISPD) standard criteria. For patients (n=37) with white blood cells (WBC) counts more than 100/mm3 as a diagnostic criteria for peritonitis, the following identification rates were observed: direct culture, 18.9% (7/37); blood culture bottle method, 75% (28/37); WBC lysis method, 78% (29/37); sedimentation method, 75% (28/37); blood agar with Tween 80, 78% (29/37); and molecular method, 86% (32/37). However in the patients (n=54) with WBC<100/mm3, the number of positive results from all the different processing and culturing methods were identical 15% (8/45), except for routine culture (0%; 0/54). A significant difference between WBC counts and the occurrence of peritonitis in patients with CAPD associated peritonitis were observed and also there was a significant difference between 16S rRNA typing (88.8% ; 40/45) and direct culture method (15.5%; 7/45) to identify pathogens in patients with CAPD associated peritonitis (P< 0.001). The lowest cost with high rate of pathogen detection was observed for blood agar with 2% Tween 80. The percentage of Gram-positive bacterial peritonitis (44.4%) was the highest followed by Gram-negative bacterial (40%) and fungal peritonitis (4.4%). By combining different laboratory and molecular methods for detection and identification of pathogens in patients on CAPD associated peritonitis, the most predominant organisms isolated were Staphylococcus aureus (7/40; 17.5%) and Escherichia coli (6/40; 15%). In conclusion: in this study, the modified laboratory methods for isolation of common bacteria and fungi peritonitis in CAPD patients showed much higher isolation and identification rate than the routine culture method. A combination of blood agar with 2% Tween 80 and 16S rRNA gene sequencing recommends these techniques to be used routinely in clinical laboratories for the diagnosis of pathogens in peritonitis cases. By combining of the modified laboratory process and 16S rRNA gene sequencing, the incidence rate of culture-negative peritonitis has decreased to less than 12% in the studied hospital, which is considered much lower than the recommended 20% by ISPD guidelines. Hence these approaches may be applied to all laboratories in Malaysia and worldwide to reduce the rate of culture-negative cases and improve the identification of etiological agents in patients with CAPD associated peritonitis.